1984
DOI: 10.1159/000309388
|View full text |Cite
|
Sign up to set email alerts
|

Central Areolar Pigment Epithelial Dystrophy (With 1 color plate)

Abstract: 7 affected and 4 normal individuals from three consecutive generations of a family with central areolar pigment epithelial dystrophy were examined. The pedigree was indicative of an autosomal dominant disorder with variable expression. The macular changes varied from numerous small drusen-like defects to large colobomatous appearing lesions while the visual acuities ranged from 6/4 to 3/120. Some of those with excellent visual acuity had small central scotomata. Urinary metabolic screening, plasma amino acid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The variable expressivity of the disease gene was further highlighted by recent findings that showed NCMD and a clinically distinct phenotype referred to as central areolar pigment epithelial dystrophy (CAPED)3 4 to occur in separate but genealogically related branches of a single large North Carolina family. 5 This has led to the conclusion that the two disorders represent a single nosological entity and, therefore, have to be considered allelic.…”
mentioning
confidence: 99%
“…The variable expressivity of the disease gene was further highlighted by recent findings that showed NCMD and a clinically distinct phenotype referred to as central areolar pigment epithelial dystrophy (CAPED)3 4 to occur in separate but genealogically related branches of a single large North Carolina family. 5 This has led to the conclusion that the two disorders represent a single nosological entity and, therefore, have to be considered allelic.…”
mentioning
confidence: 99%
“…5 Extensive genealogical studies have revealed that several other diseases, thought originally to be distinct entities, central areolar pigment epithelial dystrophy, 6 central pigment epithelial and choroidal degeneration, 7 and central retinal pigment epithelial dystrophy, 8 arise in descendants of the original NCMD founders and are in fact manifestations of the variable expressivity of the condition. 9 Subsequently, families with NCMD unrelated to the original pedigree have been reported in the United Kingdom, 10 Texas, United States, 11 Central America, 12 and France.…”
Section: -2mentioning
confidence: 99%